New archive documents about the conflict between kalmyks and kuban nogais in 1713–1714 (based on materials of the Russian state archive of ancient acts) - Kirill Stankov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Russian historians pay more and more attention to the insuffi ciently investigated problem of history of small nations of Russia and particularly to their relations with neighbour states and their subjects and vassals in modern time. The aim of this article is to attract attention of specialists in the Russian history as well as of those who specialise in Eurasian nomadic societies to the new archive documents concerning the confrontation of Kalmyks and Nogais in the context of Russian-Turkish relations at the beginning of the 18th century. The previous studies underestimated this confl ict which vivdly illustrates the tension on the south borders of Russia since the period of Peter the Great. His government tried to resolve this border confl ict by putting diplomatic pressure on Turkey (the Kuban Horde then lived on the territory of the Turkish vassal, the Crimean Khanate), but these attempts were not eff ective. The only means to resolve this problem was to directly send military help to Kalmyks against their belligerent neighbours. However, the Russian government was not ready to take this step because it could lead to a new war with the Osman Empire.